The Effect of Student-Centred Methods and Techniques on Primary School Students' Mathematics Achievement: A Meta-Analysis Study - Ulum, Hakan; Tümkaya, Songül (Malikussaleh Journal of Mathematics Learning (MJML), 2022)
The purpose of this study was to synthesize experimental studies that explain the effect of student-centred methods and techniques used in primary school mathematics courses on academic achievement. Some certain criteria were selected and applied regarding the inclusion of primary study in the synthesis. As a result of qualitative systematic review, data of the study were obtained from 63 studies that meet the inclusion criteria. The reliability of the coding protocol in the study was procured in two stages by assessing the "inter-coder reliability". The reliability (AR) was assessed as 0.88 and was considered sufficient (AR> .80).  The validation of the study was provided by publication bias and quality assessment in primary studies, language bias, time delay bias, and database bias. There was no evidence of bias. Meta-analysis results showed that student-centred strategy, methods or techniques were more effective than traditional teaching methods. The effect size was evaluated using 66 effect sizes from 63 studies and was found to be 0.787 under the random-effect model. The overall impact value attained indicates a wide and medium level of impact according to various classifications. In the moderator variables analysis, except for the moderator of the application approach, there was no significant difference found for the moderators of application time, type of publication, database, and grade level, the scale used, and school starting age, country, and sample size.